2021
DOI: 10.1002/ptr.7121
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and cancer biology: Focusing regulatory effects in different signalling pathways

Abstract: Cancer is the second‐leading cause of death worldwide. Till date, many such effective treatments are available, for example chemotherapy, surgery, and radiation therapy, but there are severe associated side effects, such as increased infection risk, constipation, hair loss, anaemia, among others. Thus, the need for effective therapeutic strategies and screening methodology arises. Researchers around the world are increasingly trying to discover anticancer therapies with as few side effects as possible and many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 87 publications
0
12
0
Order By: Relevance
“…Despite this, as such compounds constitute roughly 70 percent of all anticancer drugs. Curcumin and chrysin are two of plant compounds that are under focus these days in many anticancer researches (Mohammadinejad et al, 2015b;Bhatia et al, 2021;Alagheband et al, 2022;Salmani Javan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, as such compounds constitute roughly 70 percent of all anticancer drugs. Curcumin and chrysin are two of plant compounds that are under focus these days in many anticancer researches (Mohammadinejad et al, 2015b;Bhatia et al, 2021;Alagheband et al, 2022;Salmani Javan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has focused on the potential of chemotherapy for this compound. [9][10][11] In some cancers, apoptosis induced by Cur can occur in two p53-dependent and independent pathways. 12,13 Induced apoptosis is time and dose-dependent and is regulated by various signalling factors.…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin, an active ingredient derived from turmeric, has been recognized for its medicinal properties, including antioxidant, anti‐inflammation, radical‐scavenging, anti-solid and -blood tumor, and so on. 5–7 The anticancer effects of curcumin mainly result from multiple biochemical mechanisms that are involved in the regulation of programmed cell death, such as apoptosis, autophagy. 5 , 7–9 Recent studies have found that curcumin can induce pyroptosis of solid tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“… 5–7 The anticancer effects of curcumin mainly result from multiple biochemical mechanisms that are involved in the regulation of programmed cell death, such as apoptosis, autophagy. 5 , 7–9 Recent studies have found that curcumin can induce pyroptosis of solid tumor cells. 10 , 11 However, it is not clear whether pyroptosis is involved in the anti-leukemia effect of curcumin.…”
Section: Introductionmentioning
confidence: 99%